Caracterização e análise do patrimônio arbóreo da malha viária urbana central do município de São Carlos-SP - Sucomine, Nivia Maria (Universidade Federal de São Carlos, 2009)
The road afforestation from the central urban area of São Carlos-SP was studied in order to know it and diagnose it in order to provide support for its maintenance and expansion. To this end, we performed a qualitative and quantitative assessment of tree cover, all its information and analysis developed and entered into a computerized database. We have found 103 different plant species in a total of 2626 individuals, 147 killed, 502 seedlings and 1977 adults. Schinus molle and Murraya paniculata were the most abundant species. For the diversity index and the average index of trees per kilometer of street obtained the values 3.18 and 26.73 respectively. The average diameter at breast height (DBH) was 21.4 cm; 55% of plants had height less than 5.40 m; 45% of the population is compound of native species and only 26 species are fructiferous. Small was the number of affected plants or plant injury, but more significant was the damage caused by the crown pruning irregular. 899 individuals were in conflict with one or more equipment around and 76% had little or no free space pavement. The results obtained it was concluded that this area has a high diversity floristic. In quantitative terms, this population was still very poor, but the overall situation of trees was satisfactory. It is recommended that an intensive program of planting of trees (with less abundant species) in the streets with the lowest level of individuals and another program for the maintenance and conservation of the stock already in place, pruning and expansion of free spaces on the sidewalks.
Characterization and analysis of heritage tree loop road of center urban city of São Carlos-SP
Keywords: Planejamento urbano; Arborização; Malha viária; Inventários; Banco de dados; Road afforestation, Inventory; Database; ENGENHARIAS